Effects of in vivo adventitial expression of recombinant endothelial nitric oxide synthase gene in cerebral arteries - Chen, Alex F. Y. (The National Academy of Sciences of the USA, 1997)
Nitric oxide (NO), synthesized from l-arginine by NO synthases (NOS), plays an essential role in the regulation of cerebrovascular tone. Adenoviral vectors have been widely used to transfer recombinant genes to different vascular beds. To determine whether the recombinant endothelial NOS (eNOS) gene can be delivered in vivo to the adventitia of cerebral arteries and functionally expressed, a replication-incompetent adenoviral vector encoding eNOS gene (AdCMVNOS) or β-galactosidase reporter gene (AdCMVLacZ) was injected into canine cerebrospinal fluid (CSF) via the cisterna magna (final viral titer in CSF, 10(9) pfu/ml). Adventitial transgene expression was demonstrated 24 h later by β-galactosidase histochemistry and quantification, eNOS immunohistochemistry, and Western blot analysis of recombinant eNOS. Electron microscopy immunogold labeling indicated that recombinant eNOS protein was expressed in adventitial fibroblasts. In AdCMVNOS-transduced arteries, basal cGMP production and bradykinin-induced relaxations were significantly augmented when compared with AdCMVLacZ-transduced vessels (P < 0.05). The increased receptor-mediated relaxations and cGMP production were inhibited by eNOS inhibitors. In addition, the increase in cGMP production was reversed in the absence of calcium, suggesting that the increased NO production did not result from inducible NOS expression. The present study demonstrates the successful in vivo transfer and functional expression of recombinant eNOS gene in large cerebral arteries. It also suggests that perivascular eNOS gene delivery via the CSF is a feasible approach that does not require interruption of cerebral blood flow.